The Effect of Using a Problem Based Learning Model on the Learning Outcomes of Fourth Grade Science and Technology Students at SD Negeri 74 Palembang - Utami, Kurnia Dwi; Harini, Bunda (Jurnal Ilmiah Teunuleh, 2023)
This study aims to determine the effect of using a problem-based learning model on the learning outcomes of IPAS students in class IV SD Negeri 74 Palembang. This research used quasi-experimental design method with nonequivalent control group design type. The population in this study were all fourth grade students of SD Negeri 74 Palembang. The sample taken in this study was 58 students who were divided into experimental and control classes. The sampling technique in this study used purposive sampling technique. The instrument used in the study was a multiple choice test. The data analysis technique in this study used the Independent Samples T-test which was first carried out normality and homogeneity tests. The results in this study showed that the pretest value of the experimental class obtained an average of 56.90 and the control class of 50.34. While the posttest value of the experimental class obtained an average of 77.59 and the control class amounted to 66.55. The results of the Independent Samples T-test calculation with a significant level of ? = 0.05 obtained a sig value. 0.002, where sig. 0,002 < 0,005. Based on the results of the Independent Samples T-test, it can be concluded that there is a significant effect of using a problem-based learning model on the learning outcomes of IPAS class IV students of SD Negeri 74 Palembang.